Development of SnO2/Multiwalled Carbon Nanotube Paper as Free Standing Anode for Lithium Ion Batteries (LIB). (10th September 2015) - Elizabeth, Indu; Mathur, R.B.; Maheshwari, P.H.; Singh, B.P.; Gopukumar, S.
Abstract: Tin oxide/Multi Walled Carbon nano tube nanocomposite (SnO2 /MWCNT) is synthesized using ethylene glycol mediated industrially viable simple process. Binder free, self-supporting and flexible SnO2 /MWCNT nanocomposite paper has been prepared by employing the vacuum filtration technique. The samples are characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Raman spectroscopy (RS), and thermal gravimetric analysis (TGA) to evaluate the structure of anode and tested for its performance in a Lithium rechargeable cell. Electrochemical measurements demonstrate that the SnO2 /MWCNT composite paper anode with 30% of SnO2 by weight delivers a specific discharge capacity of ∼420 mAh g −1 up to the investigated 50 cycles at a current density of 100 mA g −1 which is ∼200 % increase in capacity as compared to pristine MWCNT anode tested under similar conditions. The application of the developed anode is demonstrated by fabricating a lithium ion pouch cell.